SOCIAL CHANGE AND FRAGMENTED COHESION (Case Study of Muslim Family Relations in Bogor City, West Java) - Muslimin, JM; Arifin, Laila Setyawati; Munawar, Wildan; Hosny Mohamed, Mahmoud Mohamed (AKADEMIKA: Jurnal Pemikiran Islam, 2020)
Entering the era of industrialization, humans live runs more pragmatically and individually. As part of gender studies, family constellation is being necessary to investigate. A significant impact can be seen from the estrangement that occurs in family relations. Family ties are felt to be increasingly loose because each person is required to have specific duties and professions to meet their needs. As a result, transformation and social change make it increasingly difficult to create intimacy like the past. The purpose of this study is to analyze the impact of social transformation on proposed divorce (cerai gugat) by wife, which is more common than divorce and social changes in family relations. The research is done by combining empirical approach and normative one. The empirical data gathered from several sources and referred to strengthen normative postulate. Where as the normative postulate is drafted to be starting point of the research. The results of this study indicate that the causes of social transformation in divorce are increased lawsuit divorce due to nushuz: wife disobedience to husband or lack of wife in carrying out their rights and obligations. Thus, increased divorce due to syiqaq: husband and wife’s quarreling.